Rekonstruksi Laporan Keuangan Berstandar SAK EMKM CV. Superindo Abadi Jember - Tuti Amalia; Diyah Probowulan; Rendy Mirwan Aspirandi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Micro, Small and Medium Enterprises (UMKM) are a form of business established by individuals or groups that are seen from the scale of home businesses and small businesses. Every business is expected to have financial reports to analyze financial performance, Financial Accounting Standards for EMKM namely, SAK EMKM. This study aims to reconstruct the financial statements and analyze the financial statements of CV. Superindo Abadi Jember is in accordance or not in accordance with SAK EMKM standards. The type of research used in this research is descriptive qualitative with a case study approach. The results of this study indicate that CV Superindo Abadi Jember is not ready to implement financial reports in accordance with the applicable SAK EMKM standards, while there are deficiencies in HR (Human Resources) who are unable to understand the preparation of financial reports that have been set in SAK EMKM. The researcher hopes that by preparing financial reports that are in accordance with standards both manually and computerized for CV Superindo Abadi Jember can be used as an example of making financial reports in the following year and can understand how important financial reports are which can later be applied for the next business continuity.